Forecasting bitcoin price considering macro economic factors and media influence using bidirectional LSTM and random forest regressor as ensemble model - Ghose, Swattic; Bin Khaled, Faiyaz; Rafin, Nafiz Imtiaz; Jawwad, Rubaiyet Hossain; Bin Yahiya, Yamin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.